MEASUREMENT OF INFORMATION SECURITY AND PRIVACY AWARENESS USING THE MULTIPLE CRITERIA DECISION ANALYSIS (MCDA) METHOD - Sukariana Yasa, I Gede Agus; Listartha, I Made Edy; Pradnyana, I Made Ardwi (Informatika, Universitas Jenderal Soedirman, 2023)
Information security is an asset that has value so it must be protected, along with increasing assets it is undeniable that many people wish to gain access and control it so that behind the convenience in the digital world there are many risks to information assets. There are several cases that occur related to information security such as data theft, illegal access, information leakage and vandalism where this becomes the privacy of the user. So it is necessary to do research from the user's perspective to measure the level of information security and privacy awareness of students and lecturers as well as recommendations that will be suggested based on the results of measuring information security and privacy awareness. The objects in this research are students and lecturers at the XYZ University. The method used is Multiple Criteria Decision Analysis (MCDA) by measuring the dimensions of knowledge, attitude, behavior in six areas of information security and three areas of privacy. Data were obtained by distributing questionnaires using a Likert scale of 5. Based on the questionnaire from the respondents, it can be seen students and lecturers have awareness that is at a